General relation between sums of figurate numbers - Mohamat Johari, Mohamat Aidil (2013)
In this study, we seek to find relations between the number of representations of a nonnegative integer n as a sum of figurate numbers of different types. Firstly, we give a relation between the number of representations, ck(n), of n as the sum k cubes and the number of representations, pk(n), of n as the sum of k triangular pyramidal numbers, namely under certain conditions